Principle, application and challenges of development siRNA-based therapeutics against bacterial and viral infections: a comprehensive review - Motamedi, Hamid; Ari, Marzie Mahdizade; Alvandi, Amirhoushang; Abiri, Ramin (Frontiers in Microbiology, 2024)
While significant progress has been made in understanding and applying gene silencing mechanisms and the treatment of human diseases, there have been still several obstacles in therapeutic use. For the first time, ONPATTRO, as the first siRNA based drug was invented in 2018 for treatment of hTTR with polyneuropathy. Additionally, four other siRNA based drugs naming Givosiran, Incilisiran, Lumasiran, and Vetriciran have been approved by the US Food and Drug Administration and the European Medicines Agency for clinical use by hitherto. In this review, we have discussed the key and promising advances in the development of siRNA-based drugs in preclinical and clinical stages, the impact of these molecules in bacterial and viral infection diseases, delivery system issues, the impact of administration methods, limitations of siRNA application and how to overcome them and a glimpse into future developments.